2016
DOI: 10.1080/15513815.2016.1223237
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Gestational Diabetes Mellitus and Maternal Obesity on Cord Blood Dynamic Thiol/Disulfide Homeostasis

Abstract: The current study suggests that the offsprings born to obese or diabetic mothers are exposed to increased oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Ozler et al (23) reported increased disulphide/native thiol and disulphide/total thiol ratios, while native thiol/total thiol decreased in the cord blood of babies born to a mother with obesity or diabetes mellitus, and associated these rates with adverse outcomes in gestational diabetes mellitus. In another study, while disulphide/native thiol and disulphide/total thiol ratios were elevated, the native thiol/total thiol ratio decreased in a group with chronic central serous chorioretinopathy group compared to healthy individuals (13).…”
Section: Discussionmentioning
confidence: 99%
“…Ozler et al (23) reported increased disulphide/native thiol and disulphide/total thiol ratios, while native thiol/total thiol decreased in the cord blood of babies born to a mother with obesity or diabetes mellitus, and associated these rates with adverse outcomes in gestational diabetes mellitus. In another study, while disulphide/native thiol and disulphide/total thiol ratios were elevated, the native thiol/total thiol ratio decreased in a group with chronic central serous chorioretinopathy group compared to healthy individuals (13).…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies investigating association between TDH and gestational diabetes mellitus [94][95][96][97]. It has been demonstrated that NT and TT levels were found to be lower than control subjects and decreased NT levels have an increased risk of possible adverse perinatal outcomes [95].…”
Section: Obstetric and Gynecologic Disordersmentioning
confidence: 99%
“…Disulfide levels were found to be higher in patients with gestational diabetes mellitus compared to healthy pregnant women and in obese pregnant compared to healthy pregnant women. Authors have suggested that infants of obese or diabetic mothers are exposed to increased oxidative stress [94]. In another study, authors have demonstrated that 50 grams glucose challenge test-positive pregnant women have increased disulfide levels after glucose loading compared to baseline [97].…”
Section: Obstetric and Gynecologic Disordersmentioning
confidence: 99%
“…In addition, a greater number of patients are needed to enlighten the role of oxidant and antioxidant systems and other possible mechanisms in the pathogenesis of psoriasis. We believe that assessment of TDHS in patients with psoriasis in terms of BMI would provide valuable data as thiol levels were found to be higher in gestational diabetes mellitus and maternal obesity in a previous report 27 . Analysis of serum levels of certain molecules containing sulfur formed after the oxidation of thiol groups, such as cysteine, cysteinylglycine, GSH, homocysteine, and ɤ-glutamylcysteine could provide further scientific data about TDHS imbalance in the etiopathogenesis of psoriasis.…”
Section: Discussionmentioning
confidence: 72%